Application of modern optimal control theory to environmental control of confined spaces and life support systems: Part 2—Basic computational algorithm of Pontryagin's maximum principle and its applications - Fan, L.T.; Hwang, Y.S.; Hwang, C.L. (Building science, 1970)
The basic form of Pontryagin's maximum principle which is a keystone of the modern optimal control theory is presented. The principle is applied to the determination of optimal control policies of several life support or environmental control systems. Three concrete examples all of which are concerned with the temperature control of a life support system consisting of an air-conditioned cabin (the system proper) subject to an impulse heat disturbance and of a heat exchanger (the control element) are considered. The first example treats the case in which the time constant of the heat exchanger is negligible. The second example considers the case in which the time constant of the heat exchanger is not ignored. In the third example the optimal policy of the system where the flow of air in the cabin can be characterized by the two completely stirred tanks-in-series (2 CST's-in-series) model is studied. In this example, the time constant of the heat exchanger is again neglected. Procedures and computational approaches employed for obtaining the optimal control policies are given in detail. On présente la forme fondamentale du principe du maximum de Pontryagin qui est la clef de la théorie moderne de contrôle optimal. Le principe est appliqué à la détermination des polices de contrôle optimal de plusieurs systèmes de support de vie ou de contrôle d'entourage. On considère trois exemples concrets dont tous se rapportent au contrôle de température d'un système de support de vie consistant d'une cabine à air conditioné (le système lui-même) soumis à une perturbation de chaleur par impulsion, et d'un échangeur de chaleur (l'élément de contrôle). Le premier exemple traite le cas dans lequel la constante de temps de l'échangeur de chaleur est négligeable. Le second exemple considère le cas où la constante de temps de l'échangeur de chaleur n'est pas ignoré. Dans le troisième exemple on étudie la police optimale du système où le courant d'air dans la cabine peut être caractérisé par les deux modèles de vaisseaux en série (2 CST en série) complèment agités. Dans cet exemple, on néglige encore la constante de temps de l'échangeur de chaleur. On donne de façon détaillée les procédés et les techniques par ordinateur employée pour obtenir les polices de contrôle optimal. Die grundlegende Form von Pontryagin's Maximum Prinzip ist dargestellt, welches der Grundstein der modernen Optimalkontrolltheorie ist. Das Prinzip wird für die Feststellung optimaler Kontrollverfahren für verschiedence Lebensunterhaltungsoder Umgebungskontrollsysteme angewandt. Drei konkrete Beispiele werden ins Auge gefasst, wobei alle sich mit der Temperaturkontrolle von Lebensunterhaltungssystemen befassen, die aus einer klimatisierten Kabine, (dem eigentlichen System) bestehen, die einem Wärmestörungsimpuls ausgesetzt wird, und aus einem Wärmeaustauscher, (dem Kontrollelement). Das erste Beispiel behandelt den Fall, in dem die Zeitkonstante des Wärmeaustauschers unbedeutend ist. Das zweite Beispiel behandelt den Fall, in dem die Zeitkonstante des Wärmeaustauschers nicht vernachlässigt wird. In dem dritten Beispiel wird das Optimalverfahren des Systems untersucht, in welchem die Luftströmung in der Kabine durch zwei gründlich gemischte Reihentanks (2 CST's-in-series) im Modell geschildert wird. In diesem Beispiel wird die Zeitkonstante des Wärmeaustauschers wieder vernachlässigt. Verfahren und berechenbare Betrach tungen zum Erhalten optimaler Kontrollverfahren werden mit Einzelheiten gegeben.